Study on routing protocol based on traffic density in VANET. (2017) - Feng, Bin; Kong, Xiangjie; Yao, Han; Li, Junyi; Peng, Jiusheng
This paper focuses on the problem of routing protocol in the VANET. For traditional GPSR protocol, due to lack of neighbour nodes in small areas with low traffic density, overall network efficiency is reduced. To address this issue, FS-GPSR protocol based on traffic density is proposed. When the vehicle is located in a large area with high traffic density, the classic GPSR protocol is used for routing and forwarding. When the vehicle is located in a small area with low traffic density, to determine the next hop node, we use an improved FS-GPSR protocol combined with the vehicle travelling direction and speed. Simulation results show that the improved FS-GPSR protocol network achieves superior performance: smaller transmission overhead and higher data delivery success rate.